Relative prices and climate policy: How the scarcity of non-market goods drives policy evaluation - Moritz A. Drupp; Martin C. Hänsel (Kiel University, Department of Economics, 2018)
We study how the scarcity of non-market goods, such as environmental amenities, affects the economic appraisal of climate policy. To this end, we perform a comprehensive analysis of the change in relative prices of non-market goods in the widespread climate-economy model DICE. We show that DICE already contains relative prices implicitly and that the impact of the scarcity of non-market goods on climate policy evaluation is therefore more pervasive than previously suggested. We calibrate DICE based on empirical evidence and propose a plausible range for relative price changes. The uncertainty is substantial, with relative price changes ranging from 1.3 to 9.6 percent in 2020. For our central calibration, the relative price change amounts to 4.4 percent in 2020. Neglecting relative prices leads to an underestimation of the social cost of carbon in 2020 of more than 40 percent. Accounting for these changes is equivalent to a decrease in pure time preference by more than a half percentage point. Our findings support initiatives to consider relative prices in governmental project appraisal and offer guidance for the evaluation of climate policy.
Keywords: Q01; Q54; H43; D61; D90; 330; climate policy; discounting; non-market goods; social cost of carbon; substitutability